An exploration of European road users' safety attitudes towards speeding. Issue 5 (4th May 2021) - Laiou, Alexandra; Theofilatos, Athanasios; Yannis, George; Meesmann, Uta; Torfs, Katrien
Abstract: The objective of this paper is to describe the attitudes and opinions of Europeans on speeding and compare them amongst countries and based on demographic characteristics as well as to provide a number of recommendations to be used in the effort to reduce speeding and improve road safety. The analysed data were collected within the E-Survey of Road Users' Attitudes (ESRA) project, a joint initiative of research organisations in 17 European countries aiming at collecting comparable (inter)national data on road users' opinions, attitudes, and behaviour with respect to road traffic risks. Data from more than 17, 000 road users were collected. The speeding aspects analysed concern acceptability of unsafe traffic behaviour related to speeding, self-declared behaviour in traffic, attitudes towards unsafe traffic behaviour, support for road safety policy measures, and reported police cheques and perceived likelihood of getting caught for speeding. All reported attitudes depend on participants' gender and age. The majority of people who accept driving over the speed limit do not believe that speed limits are set at acceptable levels. The ESRA results are also compared to those of previous similar studies. Finally, key recommendations concerning speeding were formulated, addressed to stakeholders at three different levels, namely, European-level, national/regional level, and particular stakeholders.